Desenvolvimento de um health index para transformador de potência - Carraro, Rodinei (2017)
This dissertation presents the development of the Health Index methodology to evaluate and classify power transformers, basing on its operation and maintenance information. The motivation behind the methodology’s development is linked to the improvement needs in the process of reinvestment deciding. A technical life extension beyond the accounting life cycle is searched also, identifying asset dangers and anticipating maintenance actions. The Health Index shows itself as particularly useful on the evaluation of power transformer parks, once the assets under danger are easily identified. The first step on Health Index Construction is the choice of input information, which must be regularly acquired, being available for the highest possible number of assets and containing relevant information about the power transformer conditions. The available models were analyzed, seeking to identify the properly evaluation methods to be used basing in the concessionary’s data collect practices. These data were processed through evaluation modules, representing each transformer’s subsystem. These evaluation modules were chosen for its representation of failing behavior and the transformer’s relevant aging mechanisms.